PpSAUR5 promotes plant growth by regulating lignin and hormone pathways - Li, Xin-Miao; Zhai, Han-Han; An, Xiu-Hong; Zhang, He; Zhang, Xueying; Wang, Pengfei; Chen, Haijiang; Tian, Yi (Frontiers in Plant Science, 2024)
Peach (Prunus persica) has a high nutritional and economic value. However, its overgrowth can lead to yield loss. Regulating the growth of peach trees is challenging. The small auxin-up RNA (SAUR) gene family is the largest family of auxin-responsive genes, which play important roles in plant growth and development. However, members of this gene family are rarely reported in peach. In this study, we investigated the role of PpSAUR5, a SAUR family member, in the growth and development of peach plants. PpSAUR5 responds to auxin and gibberellin, promoting and inhibiting the synthesis of gibberellin and auxin, respectively. The heterologous transformation of PpSAUR5 in Arabidopsis led to enhanced growth of leaves and siliques, lightening of leaf color, decrease in chlorophyll content, increase in lignin content, abnormalities in the floral organs, and distortion of the inflorescence axis. Transcriptome data analysis of PpSAUR5 overexpression and wild-type lines revealed 854 differentially expressed genes (DEGs). GO and KEGG analyses showed that the DEGs were primarily involved in biological processes, such as cellular processes, metabolic processes, response to stimuli, and catalytic activity. These genes were mainly enriched in pathways, such as phenylalanine biosynthesis, phytohormone signaling, MAPK signaling, and so on. In summary, these results suggested that PpSAUR5 might regulate tree vigor by modulating the synthesis of auxin and gibberellin. Future studies can use PpSAUR5 as a candidate gene to elucidate the potential regulatory mechanisms underlying peach tree vigor.